An evolutionary model for the gamma-ray system psr j1311-3430 and its companion - Benvenuto, Omar Gustavo (2013)
The most recent member of the millisecond pulsar with very low mass companions and short orbital periods class, PSR J1311−3430 (Pletsch et al. 2012) is a remarkable object in various senses. Besides being the first discovered in gamma rays, its measured features include the very low or absent hydrogen content. We show in this Letter that this important piece of information leads to a very restricted range of initial periods for a given donor mass. For that purpose, we calculate in detail the evolution of the binary system self-consistently, including mass transfer and evaporation, finding the features of the new evolutionary path leading to the observed configuration. It is also important to remark that the detailed evolutionary history of the system naturally leads to a high final pulsar mass, as it seems to be demanded by observations.